2022
DOI: 10.1186/s13048-022-01026-9
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, dynamics and recurrences of reverse cleavage in aneuploid, mosaic and euploid blastocysts, and its relationship with embryo quality

Abstract: Background During embryonic development, the normality of cleavage and the ploidy state are closely related to the final clinical outcome. At present, many research teams are focusing on the combined application of timelapse (TL) technology and preimplantation genetic testing (PGT) technology, hoping to find a connection between the two aspects of morphodynamics and genes. In the process of embryonic cleavage, there is a common abnormal cleavage pattern called reverse cleavage (RC). RC refers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Previous studies in humans suggest that reverse cleavage is associated with decreased cytoskeleton function, in particular, that of the actomyosin component, which is responsible for cytokinesis progression. Such an alteration might lead to polyploidy and chromosomal mosaicism or to an abnormality in the cell membrane [ 44 ]. Recent study in human, reported that about 25.9% of the developed blastocysts underwent reverse cleavage through the 3-first divisions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in humans suggest that reverse cleavage is associated with decreased cytoskeleton function, in particular, that of the actomyosin component, which is responsible for cytokinesis progression. Such an alteration might lead to polyploidy and chromosomal mosaicism or to an abnormality in the cell membrane [ 44 ]. Recent study in human, reported that about 25.9% of the developed blastocysts underwent reverse cleavage through the 3-first divisions.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with some limited studies in humans [ 56 , 57 , 58 ]. Conflict in the literature, however, exists with some clinical data showing that reverse cleavage cannot be used as a deselection criterion and that the presence of reverse cleavage is not associated with increased aneuploidy rates [ 59 , 60 ]. At the time of writing, the only comparable study in livestock indicated that reverse cleavage in cattle embryos reduced the incidence of hatching, increased blastocyst collapse and chromosomal aneuploidy [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other categories of qualitative parameters used for TLI embryo selection, ABNCL patterns are relatively better defined and clinically applied ( ESHRE Working group on Time-lapse technology, 2020 ). It is well reported that ABNCL leads to a myriad of adverse outcomes such as reduced blastulation ( Meseguer et al , 2011 ; Athayde Wirka et al , 2014 ; Shavit et al , 2023 ), lower blastocyst quality ( Ho et al , 2018 ; Jin et al , 2022 ), and decreased implantation potential when transferring at the cleavage stage ( Rubio et al , 2012 ; Liu et al , 2014 , 2015 ; Fan et al , 2016 ; Barrie et al , 2017 ). Previous studies have focused on the incidence of DC at the 1-cell and 2-cell stage ( Athayde Wirka et al , 2014 ; Fan et al , 2016 ), while few have considered the combined impacts of different ABNCL types up to Day 3 or beyond the 4-cell stage by a structured classification system.…”
Section: Introductionmentioning
confidence: 99%